Protection of Children in Indonesia Through Child-friendly Family - Erdianti, Ratri Novita; Anggraeny, Isdian (KnE Social Sciences, 2024)
Minister of Empowerment of Women and Children No. 11 of 2011 concerning childfriendly City/District Policy is part of a government policy that aims to protect children in all aspects of life. Child-friendly districts/cities (KLA) are those that have a development system based on children’s rights through the integration of government, community, and business commitments and resources that are planned comprehensively and sustainably in policies, programs, and activities to ensure the fulfillment of children’s rights. The KLA is basically based on fulfilling children’s rights, covering civil rights and freedoms, family environment and alternative care, basic health and welfare, education, usage of leisure time, cultural activities, and special protection. To build a child-friendly district or city requires a village’s existence to realize the fulfillment of a child-friendly city. A child-friendly village (DLA) is a village and sub-district development that brings together the commitment and resources of the village government, the community, and the business community in the framework of fulfilling children’s rights, protecting children from acts of violence, exploitation, and abuse. Hearing children’s opinions, which are planned consciously, comprehensively, and continuously. To create a child-friendly village community, participation in establishing child-friendly homes will greatly influence success in learning child-friendly villages. Keywords: protect, children, child-friendly family